Meconium peritonitis: prenatal diagnosis and postnatal management--a case report - Ramesh, J.C.; Chow, T.W.; Yik, Y.I.; Ramanujam, T.M. (Malaysian Medical Association, 1999)
The management of a case of antenatally diagnosed meconium peritonitis (MP) due to intrauterine intestinal perforation secondary to bowel atresia is reported. The literature is reviewed with reference to the significance and outcome of antenatally diagnosed MP.